Determination of Faraday Effect on Optical Properties for Polymers Blend Doping Metal Nanoparticles: A Descriptive Study - Hasan, Zaid A. (New Trends in Physical Science Research Vol. 7, 2022)
Present study highlights the Faraday effect use a magnetic field, this effect is clearly a appear through of the results. The optical properties test without magnetic field is appear the absorptance is direct proportionality with the concentration, while find the anther optical properties is inversely proportionality. Many electro-optic systems rely on the faraday effect as their foundation, which gives metal nanoparticles (NPs) and ferromagnetic (FM) polymers relevance in nanostructures.